GENDER PERSPECTIVES ON THE FORMS, PROCESSES AND VIEWS OF HANDLING SEXUAL VIOLENCE AT SURABAYA AVIATION POLYTECHNIC - Suprapto, Yuyun; Mintje, Quirina Ariantji Patricia; Rahayu, Sri; Rahmawati, Ema; Ariestyawati, Niken (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
Sexual violence in higher education has become a serious problem and requires serious attention from various parties. Educational institutions, including the Aviation Polytechnic of Surabaya, are not immune from this problem. This study was conducted with the aim of identifying gender perspectives on the forms, processes, and views related to the handling of sexual violence at the Aviation Polytechnic of Surabaya. Through a survey method involving 131 respondents (73 men and 58 women), this study revealed that sexual harassment, both verbal and physical, still occurs frequently in the campus environment. As many as 64% of female respondents and 72% of male respondents reported that they had witnessed or experienced verbal harassment in the form of sexual advances or jokes. In addition, physical harassment was reported by 24% of female respondents and 10% of male respondents. However, only 32% of all respondents were aware of the formal reporting mechanisms available at the institution. These findings highlight the gap between incidents of sexual violence and knowledge and use of existing reporting mechanisms. Therefore, this study recommends the need for increased education regarding sexual violence reporting procedures as well as strengthening regulations and preventive measures in the educational environment. The results of the study are expected to make a real contribution in improving the protection and handling system of sexual violence in educational institutions, especially Aviation Polytechnic Surabaya.